Multipspectral studies of western limb and farside maria from Galileo Earth-Moon Encounter 1 - Williams, D.A.(1); Greeley, R.(1); Neukum, G.; Wagner, R.; Kadel, S. D.(1) (American Geophysical Union, Washington, USA, 1995)
New visible and near-infrared multispectral images of the Moon obtained by the Galileo solid-state imaging system, along with lunar orbiter images (for crater counts), and spectral mixing analyses wereused to characterize western limb and eastern farside maria to determine compositional and age relationships in selected regions. Results indicate that (1) western limb mare deposits have less variability in titanium content (<2-7 wt%TiO2) and age (2.79-3.86 Ga) than areally extensive maria on the nearside; (2) areally extensive basin-filling maria generally have higher titanium contentsthan smaller, crater-filling mare patches and ponds; (3) ancient maria coveredby highland material (cryptomaria) may be present in the Mendel-Rydberg and South Pole-aitken basins; and (4) maria with compositional and age variations occur in the Grimaldi, Crueger, Mendel-Rydberg, and Apollo regions. No extensive high-titanium (>6 wt% TiO2) mare basalts were observed on the western limb and farside, which may reflect the inability of such ddenser magmas to penetrate the thicker farside crust.